Readings in personnel management - Greenlaw, Paul Stephen (Philadelphia : W. B. Saunders, 1979)
This article focuses upon two key issues: the increasing importance of human resources planning and development in organizational effectiveness, and how the major components of a human resource planning and development system should be coordinated for maximum effectiveness.
Includes bibliographical references.
hza 13/08/2018
Loans
Keywords: Personnel management